Pediatric Pulmonary Emboli at Autopsy: An Update and Case Series Review. Issue 3 (March 2019) - O'Conor, Christopher J.; Zhou, Huifang; Ritter, Jon; Dehner, Louis; He, Mai
Abstract : Objectives: Identify and characterize pediatric pulmonary emboli present at autopsy. Design: Retrospective single institution observational study with clinicopathologic correlation. Setting: Tertiary medical center. Patients: All autopsy cases performed at Washington University from 1997 to 2017 in pediatric patients (⩽ 18 yr old). Main Results: Of 1, 763 pediatric autopsies, 13 cases of pulmonary emboli were identified, including thromboemboli (6/13, 46.1%), septic emboli (3/13, 23.1%), fat emboli, and foreign body emboli. Conclusions: Pulmonary embolus is a relatively rare but potentially fatal cause of death in pediatric age patients and is often associated with congenital abnormalities, malignancy, or recent surgical procedures. Half of the fatal pulmonary emboli found in our series (3/6) show microscopic and diffuse, rather than large central or saddle emboli, potentially make a clinicoradiographic diagnosis more difficult. This series is also the first to report a case of hemostatic matrix pulmonary embolism in a pediatric age patient.